2017
DOI: 10.21608/jpp.2017.41089
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Application of Proline or Potassium in Alleviating the Adverse Effects of Irrigation Interval on Wheat Plants

Abstract: Drought stress is one of the most harmful factors of plant growth and productivity. Two pot experiments were carried out at greenhouse of agriculture botany department, faculty of agriculture, zagazig university, Sharkya Governorate, Egypt, during two successive winter seasons (2014/2015 and 2015/2016), to study the role of proline or potassium in mitigation the harmful impact of drought stress conditions on wheat plants c.v Misr 2 grown in Egypt. Growth parameters, yield and biochemical constituents were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
2
1
Order By: Relevance
“…Therefore, as a result of the many benefits mentioned earlier of applying KH, plants work on reducing the level of proline, which is considered a guide for improving plant conditions. In this regard, this study is not consistent with other studies claiming that applying K to stress plants leads to an increase in proline levels, as mentioned by (Bahrami and Hajiboland 2017;Desoky et al 2017;Jan et al 2019). In this concern, previous studies demonstrated that the relationship between proline and K varies and depends on such factors as (the taken plants part, the application methodology, and the used concentrations of K).…”
Section: Discussioncontrasting
confidence: 98%
“…Therefore, as a result of the many benefits mentioned earlier of applying KH, plants work on reducing the level of proline, which is considered a guide for improving plant conditions. In this regard, this study is not consistent with other studies claiming that applying K to stress plants leads to an increase in proline levels, as mentioned by (Bahrami and Hajiboland 2017;Desoky et al 2017;Jan et al 2019). In this concern, previous studies demonstrated that the relationship between proline and K varies and depends on such factors as (the taken plants part, the application methodology, and the used concentrations of K).…”
Section: Discussioncontrasting
confidence: 98%
“…This may due to the role of proline in plant development particulary in reproductive phase also, play vital role in response of plant to environmental stress and protein synthesis. Similar results were obtained by (Desoky et al, 2017), (Arif Shafi et al,2017) and (Khaled et al, 2020) sowing dates and plant methods (A×B) had a significant effect on oil % and oil yield (kg/fed. in both seasons.…”
Section: Seeds Oil Percentage (%)supporting
confidence: 83%
“…Proline accumulates when the amount of free amino acids in plant tissues increases with salt because higher salinity slows down protein synthesis (El-Leboudi et al, 1997). Farhad et al (2015), exogenous application of proline significantly boosted wheat growth, yield components including grain and straw yields, and these effects were positively correlated with higher percentages and absorption of N, P, K, and S. According to Desoky et al (2017), wheat's growth and production were improved by applying proline to the leaves at a rate of 0.2%, reducing the harmful impacts of drought stress.…”
Section: Introductionmentioning
confidence: 99%